Macroscopic and microscopic investigation of Cr(VI) immobilization by nanoscaled zero-valent iron supported zeolite MCM-41 via batch, visual, XPS and EXAFS techniques. (20th April 2018) - Chen, Zhongshan; Wei, Dongli; Li, Qian; Wang, Xiangxue; Yu, Shujun; Liu, Lu; Liu, Bei; Xie, Shengyu; Wang, Jian; Chen, Diyun; Hayat, Tasawar; Wang, Xiangke
Abstract: The nanoscaled zero-valent iron (nZVI) supported zeolite MCM-41 composites (nZVI/MCM) were synthesized, and applied for the immobilization of Cr(VI) from aqueous solutions. The precise role of MCM-41 and nZVI in the immobilization and reduction of Cr(VI) was characterized using SEM, TEM, HRTEM, HRTEM-EDS, XPS and EXAFS techniques. Comparing to the bare nZVI nanoparticles, the as-synthesized nZVI/MCM composites showed higher efficiency on Cr(VI) immobilization due to the high synergistic effect of Cr(VI) reduction by nZVI and sorption by MCM-41. The morphology and visualizing analysis indicated that nZVI was uniformly distributed on the surfaces of MCM-41, which reduced the aggregation of nZVI apparently and thereby increased the reduction activity. XPS and EXAFS analysis showed that nZVI could promote Cr(VI) reduction into Cr(III), and the sorption and reduction reactions were occurred on bare nZVI. MCM-41 acted as a scavenger for the insoluble products, which could improve the reduction activity of nZVI. The high performance of nZVI/MCM composites showed the promising strategy for the efficient decontamination of Cr(VI) pollution in environmental pollution cleanup. Graphical abstract: Image Highlights: nZVI/MCM composites were synthesized by a eco-friendly in-situ reduction method. Cr(VI) removal by nZVI/MCM was attributed to both sorption and reduction. nZVI/MCM exhibited high efficiency on Cr(VI) immobilization. The high dispersion of nZVI on MCM-41 surface enhanced Cr(VI) reduction. nZVI/MCM is suitable material for metal ion immobilization in pollution cleanup.